Adults vaccination in primary care: amid and beyond the pandemic - Blanco-Betancur, Mariana (2022)
Immunization is one of the most important advances in medicine, achieving protection against numerous microorganisms that have put the health of the population at risk for centuries and is currently one of the main health prevention strategies; Recently, with the appearance of COVID-19, a before and after has been marked, since vaccination has regained visibility and importance after the pandemic. However, despite the available evidence, there is limited dissemination and promotion of vaccination in the adult, a situation that generates low coverage in this population. The current global context sets an urgent call to strengthen the implementation of vaccination plans and strategies not only in the pediatric population, but also in the adult population, so the objective of this narrative review is to synthesize the current recommendations for vaccination in the population. from Colombia and Latin America with a focus on primary care in the adult population. For this, a bibliographic search was carried out in the PubMed, Science direct, Redalyc, Scielo and academic Google databases; Including studies related to vaccination in adults in Colombia and Latin America, which allow to propose systematized vaccination strategies in primary care.